Still flying blind after all these years: The Federal Reserve's continuing experiments with unobservables - Dimitri Basil Papadimitriou; L. Randall Wray (Levy Economics Institute of Bard College, 2021)
Institute President Dimitri B. Papadimitriou and Senior Scholar L. Randall Wray contend that the prevailing approach to monetary policy and inflation is influenced by a set of concepts that are a poor guide to action. In this policy brief, they examine two previous cases in which the Federal Reserve misread the data and raised rates too soon, as well as the evolution of the Fed's thought and practice over the past three decades-a period in which the central bank has increasingly turned to unobservable indicators that are supposed to predict inflation. Noting that their criticisms have now been raised by the Fed's own members and research staff, the authors highlight the ways in which we need to rethink our overall framework for monetary and fiscal policy. The Fed has far less control over inflation than is presumed, they argue, and, at worst, might have the whole inflation-fighting strategy backwards. Managing inflation, they conclude, should not be left entirely in the hands of central banks.
Keywords: 330; inflation; monetary policy; central banking